1999
DOI: 10.1177/074823379901500115
|View full text |Cite
|
Sign up to set email alerts
|

The functional and structural observations of the neonatal reproductive system of alligators exposed in ovo to atrazine, 2,4-D, or estradiol

Abstract: Wild alligators exposed to persistent organochlorine contaminants, municipal waste compounds, and contemporary-use herbicides exhibit reproductive alterations that are thought to be caused by endocrine disruption. This study tests the hypothesis that these alterations, at least in part, result from exposure of alligator embryos to contemporary-use herbicides. Alligator eggs were collected early in development, exposed to estradiol-17β, atrazine, or 2,4-D (at dosages of 0.14, 1.4, and 14 ppm, plus a dosage of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Thus, the presence of exogenous hormone or hormone agonist/antagonist in the egg could alter normal endocrine function and, ultimately, influence gender determination. Indeed, exposure‐dependent increases in the proportion of females were observed when reptilian eggs were treated with 17β‐estradiol during incubation at male‐producing temperatures [8,11,13–30]. At incubation temperatures that typically produce a 1:1 sex ratio, treatment with nonaromatizable androgens increased the proportion of males [19,23,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the presence of exogenous hormone or hormone agonist/antagonist in the egg could alter normal endocrine function and, ultimately, influence gender determination. Indeed, exposure‐dependent increases in the proportion of females were observed when reptilian eggs were treated with 17β‐estradiol during incubation at male‐producing temperatures [8,11,13–30]. At incubation temperatures that typically produce a 1:1 sex ratio, treatment with nonaromatizable androgens increased the proportion of males [19,23,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Crain et al 1997 andSpiteri et al 1999 reported results after dosing alligator's eggs with 2,4-D. Estradiol was used as a positive control. In the first study, on pipping, chorio-allantoic fluid was analyzed and blood from hatchlings (10-days post hatch) was analyzed for estradiol.…”
Section: Ecotoxicological Studiesmentioning
confidence: 99%
“…Crain et al (1997Crain et al ( , 1999 and Spiteri et al (1999) reported results after dosing alligator's eggs with 2,4-D. Estradiol was used as a positive control for estrogen pathway mediated effects; there was no positive control for androgen-mediated effects. In the first study, at pipping, chorio-allantoic fluid was analyzed and blood from hatchlings (10 days post hatch) was analyzed for testosterone.…”
Section: Ecotoxicological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high mobility and long half life in soil, residues of atrazine and its metabolites have been detected in soil, surface water and groundwater years after their initial application [2]. In addition, there is some evidence which suggests that atrazine may be an endocrine-disrupting chemical, consequently, it might be harmful to human and animals [3,4]. With regard to these problems, the studies focus on efficient bioremediation strategies for atrazine polluted environments and reducing its contamination to safe level revealed their urgency.…”
Section: Introductionmentioning
confidence: 99%